Teleworking: The Link between Worker, Family and Company. - Herrera-Ballesteros, Juan; De-las-Heras-Rosas, Carlos Javier; Rodríguez-Fernández, María Mercedes; Ciruela-Lorenzo, Antonio Manuel (MDPI, 2022)
Telework is presented as a model of work organisation that changes the paradigms of business culture in many organisations, reshaping established management and social systems. The COVID-19 pandemic and the restrictions applied to the mobility and concentration of people have accelerated the implementation of telework, generating an accelerated change in organisational models. Telework dynamics significantly transform many aspects of the business, social and personal environment. The research community has investigated: work performance; the environment; technology; social factors; and work–life balance, among other issues. However, it is necessary to know in greater depth what the most salient aspects related to telework are. To this end, a total of 539 publications from theWeb of Science database between 1984 and 2021 were analysed using bibliometric techniques. The results obtained indicate an outstanding interest in this subject in the last two years. The research comes from many different areas of knowledge and mainly focused on issues related to worker–employer–family conflict, work–life balance and flexibility policies. There has been remarkable growth and dispersion in telework research, where, in addition to productivity-based approaches, the field of study has opened up to other issues such as worker health and satisfaction, professional isolation, the role of supervisors or the gender perspective, among others. The contribution of this research is broadening knowledge about the dynamics of telework in organisations and the issues that have been the most considered by the scientific community, so that it can serve as a point of support for future research
Keywords: Teletrabajo - Aspectos psicológicos; Trabajo - Organización; Psicología de las organizaciones; SciMAT; Telework; Job flexibility; Work–life balance; Bibliometric; Work organisation